2011
DOI: 10.1177/1461444811425221
|View full text |Cite
|
Sign up to set email alerts
|

The production of pro-suicide content on the internet: A counter-discourse activity

Abstract: Pro-suicide websites are topping search engine result lists, raising fears about the internet's detrimental influence on behaviour and attitudes related to suicide. Based on a qualitative analysis, this article argues that the production of pro-suicide content on the internet should be seen as a counter-discourse, directed against socially dominant perceptions of suicide. On pro-suicide websites, the description of technical, chemical and anatomic details, the expression of honourable and clearly individualist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…With these queries, we suspect that those who accessed the websites might not have an intent to die. Westerlund [40] has suggested that the fascination with pro-suicide content, particularly the morbid and violent descriptions may be a manifestation of a meaningful process in which the producer or consumer of this content is building an identity, acting out aggressive impulses, or even rebelling against the dominant culture. An interesting future study would be to explore the motivations behind why non-suicidal individuals access suicide-related information.…”
Section: Discussionmentioning
confidence: 99%
“…With these queries, we suspect that those who accessed the websites might not have an intent to die. Westerlund [40] has suggested that the fascination with pro-suicide content, particularly the morbid and violent descriptions may be a manifestation of a meaningful process in which the producer or consumer of this content is building an identity, acting out aggressive impulses, or even rebelling against the dominant culture. An interesting future study would be to explore the motivations behind why non-suicidal individuals access suicide-related information.…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of coding, blogs were treated as individual websites. For the present study, definitions of the terms pro-suicide and anti-suicide were based on the existing literature (Westerlund 2011;Alao et al 2006;Becker et al 2004;Recupero, Harms, and Noble 2008;Aitken 2009;Thompson 1999). However, given potential ambiguity in terms that have been used to describe pro-suicide websites (e.g., facilitation of suicide), we defined pro-suicide orientations as "explicitly encouraging suicide or discouraging help-seeking" and anti-suicide orientations as "explicitly discouraging suicide and encouraging help-seeking".…”
Section: Table 1 Herementioning
confidence: 99%
“…This information is also often unmoderated, which has prompted concerns over its potential effects on users. Research surrounding the issue of the impact of the Internet on suicide has often debated the potential benefits of anti-suicide or suicide prevention websites and the potential dangers of websites that might encourage or facilitate suicide ("pro-suicide") (Aitken 2009;Luxton, June, and Fairall 2012;Recupero, Harms, and Noble 2008;Thompson 1999;Westerlund 2011). In order to gauge the potential risks of the Internet to people who feel suicidal, previous work has examined the online availability of these so called "pro-suicide" websites.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have commented on the emergence of pro-suicide websites on the Internet and the risks this may entail (Baume et al 1997;Thompson 1999;Biddle et al 2008;Recupero et al 2008;Westerlund & Wasserman 2009;Hagihara et al 2012). These sites recommend suicide as a solution to life's problems; they contain detailed descriptions of methods for achieving maximum effect, as well as suicide notes and pictures of people who have committed suicide (Westerlund 2012). Pro-suicide websites encourage and strengthen peer group pressure to fulfil suicide plans, glorifying those who have killed themselves, and a new form of suicide pact -"net suicide" -has been established (Lee 2003;Rajagopol 2004;Naito 2007).…”
Section: Introductionmentioning
confidence: 99%